Entrepreneurship Support - Paul Jones (Systemic Entrepreneurship: Contemporary Issues and Case Studies, 2015)
When referring to ‘entrepreneurship support’ the support in the majority of cases refers to activities associated with the individual entrepreneur. Although the individual entrepreneur is important they represent only one of the sub-systems within the total entrepreneurial eco-system. In this chapter, a specific subset of an entrepreneurial eco-system was discussed that can support the accelerated and coordinated manner in which entrepreneurial activities are approached in a Higher Education Institutions (HEI). This eco-system can support institutions to map and coordinate the journey of potential entrepreneurs within the specific institution. This entrepreneurial eco-system should be complemented by contents considerations that focus specifically on promoting systemic entrepreneurship such as the examples being used in lecture rooms and the business ideas supported.